“Gourmet” predation of Liolaemus lizards in the Puna Region of northwestern Argentina - Valdecantos, Maria Soledad (2024)
Birds are frequent predators on lizards (FigueroaRojas and Corales Stappung, 2004; Bianchini, 2014; Santoyo-Brito et al., 2014; Valladares Faúndez et al., 2015; Troncoso-Palacios et al., 2020) and some leave explicit, unconsumed leftovers in tree branches and bushes (e.g., the head; Young et al., 2004). Here we document the profigate consumption by a bird species of the internal organs and tails of Liolaemus lizards by analyzing desiccated remains of individuals found in the branches of shrubs...